Pengaruh Perlakuan Skarifikasi Fisik dan Lama Perendaman Air Kelapa Terhadap Viabilitas Benih Sirsak (Annona muricata L.) - Kartina, Kartina; Yenny, Ratna Fitry; Salsabila, Zahwa (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2023)
This research was aimed to know the effect of Physical Scarification and Soaking Time of Coconut Water to Viability of Soursop Seed (Annona muricata L.). This research was carried out from March until April 2022 at the Greenhouse of Faculty of Agriculture University of Sultan Ageng Tirtayasa. The research used a Completely Randomized Design (CRD) consisting of two factors. The first factor was the physical scarification, which consists of 3 levels namely S0 (Without scarification), S1 (Sanding one side of the seed), and S2 (Sanding two sides seed). The second factor was soaking time of coconut water, which consists of 3 levels namely L0 (Without soaking), L1 (Soaking time 12 hours), and L2 (Soaking time 24 hours). The combination of the two factors was repeated three times, so that 27 experimental units are obtained. The result showed that the scarification treatment with sanding one side of the seed (S1) gave the best effect on the parameters of germination age (18.22 days), maximum growth potential (58.89%), power of germination (55.56%), normal sprout (51.11%), growth rate (1.70%/day), and seeds that did not grow (44.44%). The soaking time of coconut water 24 hours (L2) gave the best effect on the parameters of germination age (17 days), maximum growth potential (61.11%), power of germination (63.33%), normal sprout (54.44%), growth rate (1.81%/day), and seeds that did not grow (38.89%). There was no interaction between the physical scarification and the soaking time of coconut water for all parameters of observed.